Optimasi Pengalaman Pengguna Pendekatan Ilmiah Mengukur Kualitas Aplikasi Shopee dengan Metode Webqual 4.0 - Geasela, Yemima Monica; Wijaya, Andy; Apriyanti, Silvia; Tanuhariono, Vincent Richard; Andry, Johanes Fernandes (JURNAL FASILKOM, 2023)
The rapid development of social media applications and features in e-commerce involves user input on social media to facilitate online buying and selling, one of which is Shopee. Shopee is one of the e-commerce platforms that engages in customer-to-customer (C2C) transactions. However, there are still several issues on the Shopee website, including not all payment options being available, delayed chat responses from sellers, and very slow order status updates. Therefore, researchers analyze the website to help Shopee assess the website's quality by analyzing user satisfaction using the Webqual 4.0 method. Using the Webqual 4.0 method, researchers will create a questionnaire consisting of usability, information quality, and service interaction. After obtaining questionnaire results from respondents, testing will be conducted on three independent variables (X) tested against one dependent variable (Y) to determine if there is an influence between variables X and Y. All tests passed and obtained valid and reliable values. The T-test conducted yielded results for H1, which is 6.574 > 2.030, meaning that H1 is accepted, indicating an influence between H1 and Y. H2, which is 6.236 > 2.030, means that H2 is accepted, indicating an effect between H2 and Y. H3, which is 6.842 > 2.030, means that H3 is accepted, indicating an influence between H3 and Y. The F-test also resulted in H0 being accepted, meaning there is an influence between X1, X2, and X3 on Y, with the results being H1, H2, and H3 on Y being 0.000 < 0.05 and F count 22.632 > F table 3.25. Based on these results, it can be concluded that Shopee website users are satisfied with the quality of the website provided by Shopee.